Occurrence of Babesia bigemina and Anaplasma marginale in clinically affected cattle in western Santa Catarina, Brazil - VANAZZI,Daniela Lourdes (2020)
ABSTRACT The objective of this study was to obtain data on the occurrence of Babesia bigemina e Anaplasma marginale in cattle with characteristic clinical signs of the disease, in different properties in western Santa Catarina. For this, 149 blood sample were collected and slides smears were done and the staining with the Romanowsky kind dye subsequently. Of the 149 samples surveyed, 78 (52.35%) were positive for A. marginale, 04 (2.68%) for B. bigemina, and 03 (2.01%) samples showed co-infection. All described cases occurred in adult animals, from two years old, with Holstein females the highest occurrence represented 119/149 (79.86%). Regarding the presence of ectoparasites, hematophagous flies were observed in all properties and ticks in 58/149 (38.92%) animals. The results showed a higher occurrence of A. marginale, evidencing the need to seek strategies of control and prevention by the veterinary professionals, especially in moments of greater occurrence of the vectors. The confirmation as from laboratory support by stained blood smears beyond being cheaper practical is a method that helping professionals identify the suspected cases etiology. Moreover, based on this information, we can promote the elaboration of prevention and treatment strategies based on simple and fast diagnostic techniques, focused on especific disease agents.